A novel online calculator to predict recurrence risk in patients with distal cholangiocarcinoma after radical pancreaticoduodenectomy. Issue 3 (7th October 2021) - Xu, Shuai; Zhang, Xiu‐Ping; Zhao, Guo‐Dong; Zou, Wen‐Bo; Zhao, Zhi‐Ming; Hu, Ming‐Gen; Gao, Yuan‐Xing; Tan, Xiang‐Long; Liu, Qu; Liu, Rong
Abstract: Background: Patients with distal cholangiocarcinoma (DCC) are prone to relapse even after radical pancreaticoduodenectomy. In this study, we sought to create an online nomogram calculator to accurately predict the recurrence risk of DCC. Methods: A total of 184 patients were included. Multivariate Cox regression analysis was used to identify independent prognosis factors for recurrence‐free survival and overall survival. A nomogram was constructed according to the prognostic factors in the training cohort and then tested in the validation cohort. Results: Multivariate Cox analysis showed preoperative carbohydrate antigen 19‐9 ( p < 0.001), maximum tumor size ( p = 0.076), perineural invasion ( p = 0.044), and N stage ( p = 0.076) were independent prognostic factors for DCC relapse. We then constructed a nomogram with these four factors. The consistency index (C‐index) of the nomogram in the training and validation cohorts were 0.703 and 0.665, respectively. Time‐dependent receiver operating characteristic and decision curve analyses revealed that the nomogram provided higher diagnostic power and net benefit compared with other staging systems. Conclusion: In this study, we developed an online nomogram calculator that can accurately predict the recurrence risk of DCC and identify patients with a high risk of recurrence in a simple and convenient manner.